Design of an Edge Slotted Waveguide Antenna Array Based on T-Shaped Cross-Section Waveguide - Teng Li; Wenbin Dou (International Journal of Antennas and Propagation)
An edge slotted waveguide antenna array based on T-shaped cross-section radiating waveguide is proposed. The T-shaped waveguide is analyzed and designed to operate in dominant mode around the center frequency, which has a lower profile compared with the rectangular one. The radiating slots are etched and rotated alternatively on the broadened top plate without cutting into the adjacent walls. The metal fences are inserted between slots to reduce the mutual coupling and surface wave. Therefore, the sidelobe level in E-plane is well suppressed. A 2 × 8 antenna array working at Ka-band is designed and fabricated. The measured results agree well with simulations which demonstrate this novel waveguide structure.